Air Semaan Al-Qur’an sebagai Terapi pada Anak dengan Gejala Attention Deficit Hyperactivity Disorder - Fashihul Lisan, Muhammad (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2024)
Water is one of the basic needs of living things. Water is also believed to have benefits as a medium for treatment or therapy for certain health problems. The Al-Qur'an recitation activity organized by the Al-Qur'an memorization group, Ikatan Hafidzah Fatayat Nahdlatul Ulama (IHF NU) Wiradesa District, Pekalongan Regency, uses water as a medium to provide blessings for those who consume it. The Al-Qur'an recitation water is used by residents as therapy for children with symptoms of Attention Deficit Hyperactivity Disorder (ADHD). This study aims to: 1) determine the practice of Al-Qur'an recitation water therapy at IHF NU Wiradesa District, Pekalongan Regency, used as therapy for children with ADHD symptoms; 2) determine the benefits of Al-Qur'an recitation water for children with ADHD symptoms. This study is a type of field research with a psychological and medical approach. Data collection techniques were carried out by interviews, analyzing documents, and observation. Data analysis of this study was carried out using quantitative and qualitative descriptive methods. The results of this study are: 1) the practice of using Al-Qur'an recitation water as therapy for children with ADHD symptoms is carried out with two interrelated activities, namely by consuming Al-Qur'an recitation water and participating in Al-Qur'an recitation activities directly; 2) in general, the practice of Al-Qur'an recitation water therapy has benefits for reducing ADHD symptoms. This can be seen from the results of the SPPAHI test on 3 children with ADHD symptoms which were carried out periodically experienced a decrease in symptoms.